A Mössbauer study of amorphous Fe40Ni40B20 - Bhatnagar A.K.; Bhanu Prasad B.; Ravi N.; Jagannathan R.; Anantharaman T.R. (My University, 2025)
Amorphous Fe40Ni40B20 (VITROVAC 0040) alloy has been investigated using 57Fe Mössbauer Spectroscopy. The Curie temperature Tc is found to be well defined and is 695 ± 1 K. The quadrupole splitting just above Tc is 0.64 mm sec-1. The crystallization temperature is 698 ± 2 K, close to but definitely above Tc. The average hyperfine field Heff(T) of the glassy state shows a temperature dependence of Heff(0)[1 - B 3 2(T/Tc) 3 2 - C 5 2(T/Tc) 5 2 - ...] indicative of the existence of spin wave excitations. The values of B 3 2 and C 5 2 are found to be 0.40 and 0.06, respectively, for T/Tc ≤ 0.72. At temperatures close to Tc, Heff(T) varies as (1 - T/Tc)β where β is one of the critical exponents and its value is found to be 0.29 ± 0.02. © 1982.